Strategi Persaingan Bisnis Tidak Sehat Dalam Novel Preambule Matoshi Family Karya Auntine Zara - Aprilia Putri Handayani; Darrel Bintang Ranjana; Eva Dwi Kurniawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to analyze how Zara in the Matoshi Family Preamble novel relates to strategies against enemies in unhealthy businesses and implementing illegal businesses. This research uses reading techniques and note-taking techniques. This research is included in qualitative research using data sources from the novel by Auntie Zara entitled Preambule Matoshi Family which was published by PT. Bukune Creative Cipta in 2023. In this research, we find out how Zara can fight business enemies who attack us unhealthy by implementing illegal business. The research results reveal various illegal business competition strategies such as smuggling illegal goods, sabotage, selling to the black market, fraud, looking for scapegoats as applied by the characters in the novel. This research provides insight into illicit business so that individuals can know the risks of implementing illicit business.